A flagship species-based approach to efficient, cost-effective biodiversity conservation in the Qinling Mountains, China. (1st March 2022) - Zhuang, Hongfei; Zhang, Chao; Jin, Xuelin; Ge, Anxin; Chen, Minhao; Ye, Jing; Qiao, Hailiang; Xiong, Ping; Zhang, Xiaofeng; Chen, Junzhi; Luan, Xiaofeng; Wang, Wei
Abstract: Prioritizing threatened species protection has been proposed as an efficient response to the global biodiversity crisis. We used in-situ conservation data to predict the potential habitat area of four flagship species: the giant panda ( Ailuropoda melanoleuca ), golden monkey ( Rhinopithecus roxella quinlingensis ), takin ( Budorcas taxicolor bedfordi ), and crested ibis ( Nipponia nippon ). We then designed systematic conservation planning schemes for various scenarios given species habitat preferences and anthropogenic activities and conducted a cost-effectiveness assessment. Broadly, the geographical distributions of suitable habitats for giant pandas, golden monkeys, and takins exhibited high spatial congruence (correlation coefficients of 0.59–0.90), and areas of high congruence were concentrated in the northern portion of the Qinling Mountains at high elevation (>1500 m). By contrast, the crested ibis was negatively correlated in space with its sympatric species (−0.47 to −0.29). Crested ibis habitats were clustered in the southern portion of the region at low elevation (<1500 m). A hypothetical conservation priority area (CPA) based on the giant panda, golden monkey, and takin included 39.64% of the Qinling Mountains and 100%, 99.99%, 99.59%, and 7.84% of the suitable habitats for giant pandas, golden monkeys, takins, and crested ibises, respectively. The same area included 99.07%, 70.87%, and 39.96% of the highly important areas for the ecosystem services of biodiversity conservation, water supply, and soil retention, respectively, and only 4.62%, 16.83%, and 13.4% of the area were associated with high-density residential area, impervious surfaces, and cropland, respectively. Therefore, we conclude that a CPA approach based on the specialist species could result in effective, low-cost biodiversity conservation in the Qinling Mountains. However, we note that existing protected areas account for only 26.52% of the CPA. We recommend that the main area of the proposed Qinling National Park should be based on the CPA developed here. Highlights: Crested ibis habitat was different from other flagship species, which with considerable areas of intensive human activities. Protecting giant pandas alone, or any flagship species, was not sufficient for long-term protection of Qinling-biodiversity. Protection cost should be considered in the designation of the conservation prioritization schemes.